Diagnostic accuracy of the Phototest for cognitive impairment and dementia in Argentina - Russo, María Julieta (2014)
Phototest is a simple, easy and very brief test with theoretical advantages over available dementia screening tests in Spain. The objective of this study was to estimate the diagnostic accuracy of the Phototest for cognitive impairment and dementia and to compare it with that of the MMSE and the Clock Drawing Test (CDT) in an Argentine population. A phase II cross-sectional study of diagnostic tests evaluation was performed in a sample of 30 controls, 61 with amnestic mild cognitive impairment (a-MCI), and 56 with mild Alzheimer type dementia (DAT). The diagnostic accuracy (DA) was assessed in relation to the clinical diagnosis by calculating the area under the ROC curve (UAC), Sensitivity (Sn), and Specificity (Sp).The DA of the Phototest for a-MCI and DAT (0.93 and 0.97 [UAC]) was higher than that of the MMSE and the CDT. The cut-off points of 27/28 for DAT (Sn = 89.29 [78.1–96.0], Sp = 96.67 [82.8–99.9]) and 30/31 for a-MCI (Sn = 85.25 [73.8–93.0], Sp = 90.00 [73.5–97.9]) maximized the sum of Sn and Sp. Phototest correlates significantly with MMSE and CDT. The Phototest is an efficient instrument for the detection of mild dementia or MCI, with good accuracy and good correlation with tests measuring overall cognitive impairment.